Photocatalytic Hydrogen Evolution by a De Novo Designed Metalloprotein that Undergoes Ni‐Mediated Oligomerization Shift. Issue 14 (6th February 2023) - Prasad, Pallavi; Hunt, Leigh Anna; Pall, Ashley E.; Ranasinghe, Maduni; Williams, Ashley E.; Stemmler, Timothy L.; Demeler, Borries; Hammer, Nathan I.; Chakraborty, Saumen
Abstract: De novo metalloprotein design involves the construction of proteins guided by specific repeat patterns of polar and apolar residues, which, upon self‐assembly, provide a suitable environment to bind metals and produce artificial metalloenzymes. While a wide range of functionalities have been realized in de novo designed metalloproteins, the functional repertoire of such constructs towards alternative energy‐relevant catalysis is currently limited. Here we show the application of de novo approach to design a functional H2 evolving protein. The design involved the assembly of an amphiphilic peptide featuring cysteines at tandem a/d sites of each helix. Intriguingly, upon Ni II addition, the oligomers shift from a major trimeric assembly to a mix of dimers and trimers. The metalloprotein produced H2 photocatalytically with a bell‐shape pH dependence, having a maximum activity at pH 5.5. Transient absorption spectroscopy is used to determine the timescales of electron transfer as a function of pH. Selective outer sphere mutations are made to probe how the local environment tunes activity. A preferential enhancement of activity is observed via steric modulation above the Ni II site, towards the N‐termini, compared to below the Ni II site towards the C‐termini. Abstract : A de novo H2 evolving metallopeptide is constructed from first principles, which undergoes oligomerization change in the presence of Ni II . Under white light, the metallopeptide produces H2 via a reductive quenching pathway. The timescales of ET and the role of thiol pKa is determined from TAS kinetics and pH titration experiments, respectively. Outer sphere steric modulation shows preferential binding of H + to Ni from N‐termini.